2015
DOI: 10.1186/s12967-015-0632-8
|View full text |Cite
|
Sign up to set email alerts
|

Phase I clinical trial of autologous NK cell therapy using novel expansion method in patients with advanced digestive cancer

Abstract: BackgroundNK cells can destroy tumor cells without prior sensitization or immunization. Tumors often lose expression of MHC molecules and/or antigens. However, NK cells can lyse tumor cells in a non-MHC-restricted manner and independent of the expression of tumor-associated antigens. NK cells are therefore considered ideal for adoptive cancer immunotherapy; however the difficulty of obtaining large numbers of fully functional NK cells that are safe to administer deters its clinical use. This phase I clinical t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
175
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 218 publications
(190 citation statements)
references
References 37 publications
5
175
0
1
Order By: Relevance
“…Clinical trials using autologous NK cells have been performed targeting solid tumors such as colorectal cancer, non-small cell lung cancer, melanoma, kidney cancer and esophageal cancer [87][88][89]. In general, autologous NK cell therapy is safe without side effects such as GvHD [87], but its therapeutic effect is limited to some cancer types [74].…”
Section: Nk Cell-based Immunotherapy: Autologous Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical trials using autologous NK cells have been performed targeting solid tumors such as colorectal cancer, non-small cell lung cancer, melanoma, kidney cancer and esophageal cancer [87][88][89]. In general, autologous NK cell therapy is safe without side effects such as GvHD [87], but its therapeutic effect is limited to some cancer types [74].…”
Section: Nk Cell-based Immunotherapy: Autologous Cellsmentioning
confidence: 99%
“…In general, autologous NK cell therapy is safe without side effects such as GvHD [87], but its therapeutic effect is limited to some cancer types [74]. An activation culture with IL-2 and OKT3 or Hsp70 has been reported to be able to efficiently induce the proliferation of NK cells [74], in particular, the retronectin culture method of Sakamoto et al showed a high amplification efficiency (about 4720-fold) [89].…”
Section: Nk Cell-based Immunotherapy: Autologous Cellsmentioning
confidence: 99%
“…These immuno ligands have demonstrated antitumour activity both in vitro and in vivo. In phase I clinical trial study conducted on advanced digestive cancer patient, NK cells infusion was well tolerated by all patients with no adverse events [17]. However, there was no clinical response was reported but nevertheless, there is still an area of improvement within the context of genetic modification for developing NK-cells based effective cancer immunotherapies as shown in Figure 1.…”
Section: Conceptual Papermentioning
confidence: 98%
“…Indeed, ex vivo cytokine activated and expanded autologous NK cells were shown to be safe; however, no clinical responses in cancer patients with metastatic melanoma, renal cell carcinoma or advance gastrointestinal cancer were seen [133,134,135]. These limitations could potentially be overcome by combination of autologous NK cells (either the patients' endogenous NK cells or reinfused autologous cells after ex vivo stimulation/expansion) in combination with a bispecific immuno-engager and optional IL-15.…”
Section: Enhancing Nk Cell Efficacy With Cytokinesmentioning
confidence: 99%